A novel big data mining framework for reconstructing large-scale daily MAIAC AOD data across China from 2000 to 2020. Issue 1 (31st December 2022) - Chen, Binjie; Ye, Yang; Tong, Cheng; Deng, Jinsong; Wang, Ke; Hong, Yang
ABSTRACT: Satellite-based aerosol optical depth (AOD) retrieval products are essential in air pollution and climate change research. Unfortunately, cloud contaminations and unfavorable surface conditions result in a considerable proportion of missing AOD data. Numerous studies have been conducted to reconstruct large-scale AOD data gaps by utilizing adjacent spatiotemporal information or modeling AOD data via various external geographical data. However, the erratic variation of AOD and the inconvenience of external data weaken the accuracy and efficiency of reconstruction. To address these issues, a novel big data based iterative variation mining framework (IVMF), utilizing multi-spatiotemporal information on AOD variations, is proposed to reconstruct large-scale AOD data over China from 2000 to 2020. Simulated and real-data experiments are carried out to validate the effectiveness and robustness of the IVMF. Results show that the spatial patterns of the reconstructed AOD are consistent with those of the original AOD in the simulated experiments. The final reconstructed AOD data strongly correlate with in-situ AOD measurements in the real-data experiments (correlation coefficient of 0.91). After reconstruction, the average daily AOD coverage increases from 30.42% to 96.69% (a 218% increase). Besides, results reveal that central China exhibits severe AOD levels, while northwest China presents low AOD levels. Overall, the proposed IVMF can largely resolve the missing AOD data problem with outstanding accuracy and efficiency, and has great potential to be generalized to other regions and remote sensing products.